Platelets are a previously unrecognised source of MIF - Strüßmann, Tim; Tillmann, Sabine; Wirtz, Theresa; Bucala, Richard; Hundelshausen, Philipp von; Bernhagen, Jürgen (Thrombosis and Haemostasis, 2013)
Macrophage migration inhibitory factor (MIF) is an inflammatory cytokine with chemokine-like functions and a role in atherogenesis. MIF is secreted by various cells including endothelial cells and macrophages. Platelets are another prominent cell type with a role in atherogenesis and are a rich source of atherogenic chemokines. We asked whether platelets express and secrete MIF. In comparison, CXCL12 release was determined. We examined the subcellular localisation of MIF in platelets/ megakaryocytes, studied its co-localisation with other plateletderived mediators and asked whether platelets contain MIF mRNA. Moreover, we probed the functional role of platelet-derived MIF in inflammatory cell recruitment. Using Western blot and ELISA, we demonstrated and quantitated MIF protein in human and mouse platelets. Applying confocal-microscopy, MIF was found to localise in granularlike structures, but did not co-localise with known platelet cytokines. qPCR indicated that platelets contain low levels of MIF mRNA. ELISA measurements from human platelet supernatants showed that, whereas thrombin and collagen triggered the release of MIF and CXCL12, ADP and oxidised LDL promoted CXCL12 but not MIF secretion. Using Transwell assays, we demonstrated that platelet supernatants promoted monocyte chemotaxis and that this was blocked by neutralising MIF antibodies. This is the first report demonstrating MIF secretion from activated platelets, suggesting that platelets are a previously unrecognised source of MIF in inflammatory processes. There are distinct activating stimuli for MIF and CXCL12 secretion. A substantial portion of the chemotactic capacity of stimulated platelet supernatants is contributed by MIF, suggesting a role for platelet-derived MIF in atherogenic cell recruitment.
Keywords: Atherosclerosis; chemokines; cytokines; inflammatory mediators; macrophage